Investigating elementary school teachers’ knowledge transformation in project-based experiential STEAM learning - Putra, Yudi Yunika (Revija za elementarno izobraževanje, 2025)
Successfully implementing project-based experiential science, technology, engineering, arts, and mathematics (STEAM) learning hinges on the teachers’ comprehension of fundamental concepts. This study investigates elementary school teachers’ knowledge transformation of project-based experiential STEAM learning after participating in a focused STEAM education workshop. Through an investigative exploration with the participation of five elementary school teachers, this study reveals that participating teachers better comprehend STEAM as an educational approach after the workshop. Meanwhile, their understanding of project-based learning decreased, and experiential learning remained unchanged. This study suggests an integrated form of training that equally addresses the interconnected components of STEAM, project-based, and experiential learning.
Keywords: experiential learning; handson activities; izkustveno učenje; praktične dejavnosti; project-based learning; projektno učenje; STEAM learning; teacher knowledge; učenje STEAM; znanje učiteljev